Early discharge after cryoablation procedure: is it safe?. (24th May 2021) - Silverio Antonio, P; Rodrigues, T; Brito, J; Pereira, S; Valente Silva, B; Alves Da Silva, P; Cunha, N; Nunes-Ferreira, A; Bernardes, A; Lima Da Silva, G; Carpinteiro, L; Cortez-Dias, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Discharge after overnight hospital stay is standard procedure in patients submitted to elective atrial fibrillation (AF) ablation. Taking into consideration the low rate of cryoablation procedure complications could the same day discharge be an option? Purpose: To access the safety of same day discharge of patients submitted to AF cryoablation. Methods: Single-center retrospective study of consecutive pts admitted to elective AF cryoablation in a tertiary center between February 2017 and November 2020. Patients were divided into two groups: same day discharge and next day discharge. Only patients submitted to ablation until 4 p.m. were included. Complication rates were obtained up to six months after the procedure. Complications were defined as death, pericardial tamponade, hematoma requiring evaluation and/or intervention, major bleeding requiring transfusion, hospital admission related to the procedure. Results: One hundred fifty-four pts were included, with a mean age of 61 ± 10.9 years, 66.2% were males, 18.2% with diabetes, 65.6% with dyslipidemia, 77.9% with hypertension, 10.4% with chronic kidney disease KDIGO stage 3 or more. Median follow-up of 436 (IQ 178 – 729) days. Most of the pts had paroxysmal (73.4%) and persistent short duration AF (23.4%). Sixty-two pts (40.3%) were early discharged and there were no differences between the two groups regarding epidemiological and clinical characteristics (p = NS). A very low rate of complications in both groups was observed, occurring in 6.5% of pts with early discharge and in 8.7% of pts in overnight stay, without statistical significance between the two groups (p = 0.61). The most frequent complications were local hematoma (5 pts, 2 in early discharged group), pericardial effusion (3 pts, all in overnight stay), femoral pseudo-aneurism (2 pts, 1 in each group) and arteriovenous fistula (1 pt in overnight stay group). The type of complications did not differ between the two groups (p = 0.51). Two pts died during the follow up, unrelated with the procedure. In addition, no difference in success rate and arrhythmic recurrence was observed between the two groups. (p = NS) Conclusion: Our study suggests that is safe to early discharge pts submitted to AF ablation, reducing the hospital stay length in selected pts. Larger studies are needed to confirm this data before routine implementation of this strategy.